Users / Patients as Industrial Relations Actors: A Structurationist Analysis - Bellemare, Guy; Briand, Louise; Havard, Christelle; Naschberger, Christine (Relations industrielles / Industrial Relations, 2018)
SummaryThis paper presents a structurationnist analysis model that aims to revise the classic industrial relations theories. The model, primarily based on the re-definition of the notion of actor in industrial relations (Bellemare, 2000), proposes to reconsider the frontiers of the industrial relations system (Bellemare and Briand, 2006; Legault and Bellemare, 2008), to replace the notion of “system” by the concept of “region,“ and to extend the model to the study of issues related to “life politics” (Giddens, 1991).The proposed model is illustrated by the study of the influence of users/patients on the work organization and on the decisions of the governing bodies of a French university hospital, and on the French health system (public policies, research priorities and methods, etc.).The results of the study show that the users/patients have become actors in the work relation regions through their mobilization on issues related to life politics: they have challenged the border between expert knowledge and common knowledge, and they have gained greater control over their health and the care they receive. Patients’ associations and individual patients, for their part, have modified the work relations regions at the organizational and worksite levels.Our results pave the way for future investigations that will integrate the dynamic conceptions of “actor” and of “regions of work relationships,“ as well as issues related to the life politics, in order to validate the generalizing scope of the model proposed.